Full-time early Childhood Education in the academic production of graduate programs in education - Auer, Franceila (2022)
The paper aims to search, analyze and synthesize the research carried out in the country and, based on this movement, draw an overview of full-time early childhood education in the various experiences that Brazilian institutions go through, as well as identify new possibilities for future research. Through a search carried out in the Catálogo de Teses e Dissertações da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES)  and in the Biblioteca Digital Brasileira de Teses e Dissertações (BDTD), 22 master’s thesis published between 2008 and 2018 were selected. It uses the Integrative Review of Literature and the software Nvivo for data analysis as method. The results indicate that obstacles are put in the implementation of policies directed to full-time early childhood education, which are reflected in the materialization of experiences in different contexts, concerning the lack of financial and material resources, inadequacy of infrastructure, unspecificity of pedagogical proposals, fragmentation of the day into shifts and urgency of professional training, tensioning a broader conception of education with socially referenced quality. It is concluded that full-time care has been used as a strategy to face poverty and social inequalities, in order to promote equity for the socioeconomically disadvantaged child population.